Standard test method for resistivity of metallically conducting resistance and contact materials (American Society of Testing Materials, 2007)
This test method covers the determination, to a precision of 2 %, of the electrical resistivity of materials used in resistors, heating elements, and electrical contacts, as well as products of powder metallurgy processes which are used for other purposes.